2019
DOI: 10.1103/physrevd.100.104052
|View full text |Cite
|
Sign up to set email alerts
|

Spinning test particles in the γ spacetime

Abstract: We consider the motion of spinning particles in the field of a well known vacuum static axially-symmetric space-time, known as γ-metric, that can be interpreted as a generalization of the Schwarzschild manifold to include prolate or oblate deformations. We derive the equations of motion for spinning test particles by using the Mathisson-Papapetrou-Dixon equations together with the Tulczyjew spin-supplementary condition, and restricting the motion to the equatorial plane. We determine the limit imposed by super… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…The total gravitational mass of the source is M = mγ and from the computation of the quadrupole moment Q = γ m 3 (1 − γ 2 )/3 one can see that values of γ < 1 (γ > 1) correspond to prolate (oblate) deformations. The properties of the ZV space-time were studied in [12][13][14][15][16][17][18][19][20], while interior solutions for the ZV metric were obtained in [42,43]. A stationary generalization of the ZV metric was obtained by Halilsoy in [37].…”
Section: Stationary Zipoy-voorhees Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…The total gravitational mass of the source is M = mγ and from the computation of the quadrupole moment Q = γ m 3 (1 − γ 2 )/3 one can see that values of γ < 1 (γ > 1) correspond to prolate (oblate) deformations. The properties of the ZV space-time were studied in [12][13][14][15][16][17][18][19][20], while interior solutions for the ZV metric were obtained in [42,43]. A stationary generalization of the ZV metric was obtained by Halilsoy in [37].…”
Section: Stationary Zipoy-voorhees Metricmentioning
confidence: 99%
“…For example in recent times some attention has been given to the Zipoy-Voorhees (ZV) metric which is a static generalization of the Schwarzschild solution to include higher multipole moments and describes the field outside prolate or oblate spheroids [10,11]. The properties of the motion of test particles in the ZV space-time and the possibility of testing the geometry from astrophysical observations has been discussed in several articles [12][13][14][15][16][17][18][19][20]. However, astrophysical compact objects typically rotate and therefore it would be more interesting to study the properties of stationary solutions.…”
Section: Introductionmentioning
confidence: 99%
“…These observations opened a qualitatively new stage to reveal black hole's unknown properties and test remarkable nature of the background geometry around black hole's horizon irrespective of the fact that there are still fundamental problems that general relativity faces, i.e., the occurrence of singularity, spacetime quantization, etc. In this framework, the motion of test particles in the strong gravitational field regime has been a productive field of study for several years [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. On the other hand, there is an extensive body of work devoted to understand the nature of radiative inspirals around black holes as a source of gravitational waves and binary systems [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Note that these spacetime metrics belong to Weyl's class of solutions [19][20][21]. Several studies in the γ-metric can be found in the recent literature: optical appearance [22], the accretion process [10,23], shadows [24,25], geodesics motion [26], spinning particle motion [27] and charged particles dynamics [28,29].…”
Section: Introductionmentioning
confidence: 99%